(untitled) (Ameghiniana, 2014)
Permian palynomorphs fromthe La Puerta Formation, Frontal Cordillera, Argentina, are reported for the first time. The palynological assemblage is mainly dominated by bisaccate and striate pollen grains. The species are: Cannanoropollis sp. cf. C. densus (Lele) Bose and Maheshwari, Cycadopites sp., Limitisporites hexagonalis Bose and Maheshwari, Lueckisporites sp., Lunatisporites sp., Pakhapites sp., Platysaccus trumpii Ottone, Potonieisporites sp., and Yittatina sp. The palynoflora is regarded as early Early Permian in age.